2009
DOI: 10.1016/j.ajhg.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Bayesian Meta-Analysis of Gene-Disease Associations

Abstract: Meta-analysis is a vital tool in genetic epidemiology. However, meta-analyses to identify gene-disease associations are compromised when contributing studies have typed partially overlapping sets of markers. Currently, only marginal analyses are possible, and these are restricted to the subset of studies typing that marker. This does not allow full use of available data and leads to the confounding of marker effects by closely associated markers. We present a Bayesian approach that exploits prior information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…Bayesian analysis was performed with the Java package “BayesMeta,” described in Newcombe et al (22). Post hoc power calculations were performed with G*power software package.…”
Section: Methodsmentioning
confidence: 99%
“…Bayesian analysis was performed with the Java package “BayesMeta,” described in Newcombe et al (22). Post hoc power calculations were performed with G*power software package.…”
Section: Methodsmentioning
confidence: 99%
“…In the current scenario for the role of PDE4D gene in the development of stroke, SNP 83 seems to be more reproducible in its association with stroke especially among the Chinese and Asians. Additionally, it has been J U S T A C C E P T E D found that meta-analysis reports too can be compromised due to partial genotyping of overlapping marker sets and so to overcome this, a multi-locus Bayesian meta-analysis approach was proposed that revealed no association despite increase in statistical power [56]. This method provided the most thorough meta-analysis for PDE4D association study in stroke which was consistent with the results obtained by Bevan et al (2008) [46].…”
Section: Pharmacology Studiesmentioning
confidence: 98%
“…The performance of the two methods is comparable and both methods correctly identify SNP 5 as the causal marker. However, it should be kept in mind that the method presented by Newcombe et al [2009] is currently only applicable under an additive genetic model assumption, and makes stronger (parametric) assumptions on the exchangeability of genotype distributions between studies. Under a multinomial‐logit transformation, haplotype frequencies are hierarchically linked via Normal distributions, all with the same variance.…”
Section: Simulationsmentioning
confidence: 99%
“…Our goal is to combine information across studies and markers to investigate the role of PDE4D in risk of stroke. Our meta‐analysis is based on an existing thorough systematic review [Newcombe et al, 2009] and incorporated nine SNPs from seven studies [Lövkvist et al, 2008; Meschia et al, 2005; Nakayama et al, 2006; Nilsson‐Ardnor et al, 2005; Saleheen et al, 2005; Staton et al, 2006; Zee et al, 2006]. As described in Bevan et al [2008] and Newcombe et al [2009], studies were identified by searching two electronic databases (PubMed Medline and EMBASE) for literature published from 1996 to August 12, 2008, by using the keywords “stroke,” “SNP polymorphism,” “PDE4D” and “phosphodiestrase 4D” in isolation and combination with one another.…”
Section: Pde4d Gene and Risk Of Strokementioning
confidence: 99%